Dakwah dalam Budaya Nu Ham Tua’ di Amarasi NTT - Fuad Fauzi Horsan (Dakwah Institut PTIQ Jakarta, 2020)
Methods and discussing Islamic da'wah in Indonesia are increasingly diverse and always interesting to study, because da'wah besides implementing Muslims in the implication of God's messages to His servants is also a deedification or concept that develops the development of the times. However, this research is more interested in traditional and conventional da'wah research carried out with heredity (inheritance) from the founder for his successors, such as in NTT Province especially in the Amarasi Kupang community, as the Da'wah Old Ham